Effect of cooking on arsenic concentration in rice - Atiaga, Oliva (2020)
This study assessed the effect of rinsing and boiling on total content of As (tAs) and of its inorganic and organic forms in different types of rice (polished and brown) from Spain and Ecuador. Rice was subjected to five different treatments. The results showed that the treatment consisting of three grain rinsing cycles followed by boiling in excess water showed a significant decrease in tAs content compared with raw rice. Regarding As species, it is worth noting that the different treatments significantly reduced the content of the most toxic forms of As. The estimated lifetime health risks indicate that pre-rinsing alone can reduce the risk by 50%, while combining it with discarding excess water can reduce the risk by 83%; therefore, the latter would be the preferable method.